The occurrence of the Rumen Ciliate Metadinium banksi Dehority 1985 (Ophryoscolecidae, Entodiniomorphida) from Domestic Goats (Capra hircus L.) in Southeastern Turkey [Türkiye'nin Güneydogusunda Yaşayan Evcil Keçilerde (Capra hircus L.) İşkembe Siliyati Metadinium banksi Dehority, 1985 (Ophryoscolecidae, Entodiniomorphida)'nin Bulunuşu] - Göçmen B.; Dehority B.A.; Rastgeldi S. (2002)
Metadinium banksi was observed in rumen contents from a single goat out of eight living in southeastern Turkey. It constituted 0.25% of the total ciliate population and had a 12.5% frequency of appearance. The size and percentage occurrence of this species in the present study are compared to those previously reported for other animal hosts living in different geographical locations. This study reports for the first time in Turkey the presence of Metadinium banksi in arctic ruminants.